Unveiling the silent threat: community awareness on non-communicable diseases / Nursyuhadah Othman… [et al.] - Othman, Nursyuhadah; Che Lamin, Roz Azinur; Muhsain, Siti Nur Fadzilah; Mokhtar, Nur ‘Ainun; Mohd Najib, Mohd Nadzri (UiTM Global @ Office of International Affairs, 2024)
Non-communicable diseases (NCDs) or chronic illnesses are characterised by their prolonged nature and are usually brought on by a combination of behavioural, physiological, environmental, metabolic and genetic variables. In this context, the World Health Organisation (WHO) and other international organisations are coordinating efforts to prevent and control complications of noncommunicable diseases (NCDs), such as diabetes mellitus and Alzheimer, with an emphasis on lowering risk factors as well as improving access to essential interventions. Moreover, The United Nations recognises that NCDs pose a substantial barrier to sustainable development and aims to decrease premature mortality from NCDs by one-third by 2030. Furthermore, besides the management by healthcare professionals, individuals with NCDs need to understand their disease along with the management of their illness. It is crucial for individuals in a society without NCDs to adopt preventive measures to avoid developing NCDs. In addition, having an in-depth knowledge and awareness of NCDs could aid individuals in assisting their loved ones with NCDs in managing their condition.